A trajectory planning algorithm for redundant manipulators - Duarte, Fernando B. M. (1999)
Redundant manipulators have some advantages when compared with classical arms because they allow the trajectory optimization, both on the free space and on the presence of obstacles, and the resolution of singularities. For this type of manipulators, several kinematic control algorithms adopt generalized inverse matrices. In this line of thought, the generalized inverse control scheme is tested through several experiments that reveal the difficulties that often arise. Motivated by these problems this paper presents a new method, that optimizes the manipulability through a least square rational function approximation, to determine the joints positions and studies the chaos revealed by the kinematics trajectory planning scheme, as well as its influence on the dynamics, when controlling redundant and hyper-redundant manipulators. The experiments confirm the superior performance of the proposed algorithm, for redundant and hyper-redundant manipulators, revealing several properties and gives a deeper insight towards the future development of superior trajectory control algorithms.